Critical variables regulating age-related anabolic responses to protein nutrition in skeletal muscle - Deane, Colleen S.; Cox, Jake; Atherton, Philip J. (Frontiers in Nutrition, 2024)
Protein nutrition is critical for the maintenance of skeletal muscle mass across the lifecourse and for the growth of muscle in response to resistance exercise – both acting via the stimulation of protein synthesis. The transient anabolic response to protein feeding may vary in magnitude and duration, depending on e.g., timing, dose, amino acid composition and delivery mode, which are in turn influenced by physical activity and age. This review aims to: i) summarise the fundamental metabolic responses of muscle to protein feeding, ii) discuss key variables regulating muscle anabolic responses to protein feeding, and iii) explore how these variables can be optimized for muscle anabolism in response to physical activity and ageing.